2010
DOI: 10.1007/s10637-010-9444-0
|View full text |Cite
|
Sign up to set email alerts
|

A dose-escalation phase I trial of nimotuzumab, an antibody against the epidermal growth factor receptor, in patients with advanced solid malignancies

Abstract: Nimotuzumab could be safety administered up to 800 mg with manageable toxicity. No relationships were found between pharmacodynamic effects on EGFR downstream signaling pathways and drug efficacy or toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…No Grade 3 toxicity was observed, and the most severe adverse events were Grade 2 tremors and hypertension [11]. Both dose escalation trials revealed that h-R3 alone could be safely administered up to at least 400 mg per week, and no correlation were found between h-R3 dosage and toxicities [10,11].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…No Grade 3 toxicity was observed, and the most severe adverse events were Grade 2 tremors and hypertension [11]. Both dose escalation trials revealed that h-R3 alone could be safely administered up to at least 400 mg per week, and no correlation were found between h-R3 dosage and toxicities [10,11].…”
Section: Discussionmentioning
confidence: 97%
“…In a clinical phase I trial, h-R3 alone could safely be administered up to highest planned dose level at 800 mg per week, although DLT was observed at 100 mg (Grade 3 fatigue) in one patient [10]. Other Grade 3 of h-R3-related adverse events were anemia (1/17 patient) and activated partial thromboplastin time prolongation (1/17 patient).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 EGFR expression was also evaluated immunohistochemically in ten NSCLC specimens in a Phase I trial of nimotuzumab plus palliative radiation therapy, but again there was no statistically significant association between EGFR expression and treatment response or outcome because of the limited sample size. 30 No definitive conclusions can thus be drawn at this time concerning the predictive utility of immunohistochemically determined EGFR expression level for the treatment of NSCLC patients with anti-EGFR mAbs, and further studies are therefore warranted.…”
Section: Predictive Biomarkers Molecular Predictors Of Responsementioning
confidence: 97%
“…Another Phase I trial was performed to assess the pharmacodynamic effects of escalating weekly intravenous doses of nimotuzumab ranging from 100 to 800 mg administered alone in Caucasian patients with advanced solid cancer. 30 Tumor and skin biopsy specimens were collected before and 3 weeks after the onset of treatment for immunohistochemical assessment of the expression of EGFR and its downstream signaling molecules. Seventeen patients were enrolled, including one who was not treated with nimotuzumab; most of the patients had colon (n = 11) or rectal (n = 2) cancer.…”
Section: Preclinical Datamentioning
confidence: 99%